Voluntary CSR vs. mandatory CSR : the sound of employees - Sarna, Bhavesh (2016)
Corporate Social Responsibility (CSR) laws are an area of exploration and there is debate over preference to voluntary CSR laws or to mandatory CSR laws. The objective is to con-duct a micro-level study to explore the employee’s preferences for mandatory CSR laws or voluntary CSR laws. There is some existing literature on this topic at the macro-level and goal is to extend and contribute to the literature about this topic by studying the pref-erence at the micro-level. A qualitative study based on semi-structured interviews was conducted with 15 employees in India and Finland. The study contributes by identifying two different kinds of typologies of employees based on their experiences with CSR and based on their awareness about CSR. The results show that maximum employees prefer the mandatory CSR laws over the voluntary CSR laws. Also, a third kind of preference ‘the diplomatic preference’ was observed among the employees. The finding supports the idea that employees like to get involved with CSR activities of the company and also they judge the CSR performance of the company. Further, the study also demonstrates that employee’s understanding of CSR is varied, whereas the existing literature considers this varied group of employees as a coherent group of stakeholders. Also, there is a correlation between social security and the need for mandatory CSR laws.